When Nurses in an Emergency Situation Look for a Medical Item But Fail to See It - Riyadh Saleh H. Almulhis Msn, RD; Modi Al-Moteri PhD, RN (SAGE Publishing, 2024)
Emergency department nurses may fail to see medical items in emergency cart drawers, such as syringes and tubes, while handling emergency situations, which can often contribute to a delay in managing the case. This is a phenomenon known as Looked-but-failed-to-see (LBFTS) and occurs when the observer fails to detect a visible visual stimulus among various other stimuli. LBFTS is a group of human errors, including inattentional blindness (IB), satisfaction of search, and biased search processes, and is associated with constraints on human visual processing. LBFTS has been studied extensively in the fields of aviation, military, radiology, and road safety; however, the role of LBFTS in hospital ED has generally been overlooked. Hence, a key aim of this study was to investigate the possibility of the occurrence of LBFTS among ED nurses while searching for a particular medical item during a real-life emergency. An observational cross-sectional blinded study was conducted to determine the occurrence of LBFTS in a real-life visual search task during resuscitation cases in ED. The A-B-C (antecedent-behavior-consequence) observation and recording naturalistic observation technique was used. A total of 45 ED nurses who were assigned to either the crash cart or the intubation trolley at the time of data collection agreed to participate and were included in the analysis. The results revealed that LBFTS accounted for 66% of the cases where emergency items were brought from another location. Participants missed seeing an item, although the item was directly in front of their eyes. Factors such as the perception of cognitive workload at the time of data collection positively impacted the increase in LBFTS ( P = .021). Taken together, the results of the present study and recent visual studies support the occurrence of LBFTS among nurses working in ED. Devising successful strategies to reduce this phenomenon could translate directly into saved lives.